2022
DOI: 10.2147/jir.s348866
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Protects Against Diabetic Cardiomyopathy by Regulating the Adipocytokine Pathway

Abstract: Purpose: Obesity and diabetes are often accompanied by chronic inflammation and insulin resistance, which lead to complications such as diabetic cardiomyopathy. Ginsenoside Rb1 has been used to treat diabetes and obesity and reduce inflammation as well as risk of heart diseases. However, the role of ginsenoside Rb1 in treating diabetic cardiomyopathy remains unclear. Methods: Diabetic mice were administered ginsenoside Rb1 for 12 weeks, and their body weight, body fat, and blood glucose levels as well as and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Inflammation is increased in DCM in vitro and vivo, and 6-G treatment reduces this inflammation. This confirms previous studies showing that inflammatory cytokines IL-1 β , IL-6, and TNF- α are elevated in DCM [ 34 , 35 ]. 6-G also has anti-inflammatory effects in other diseases such as sepsis, cerebral ischemia/reperfusion injury, and diabetic nephropathy [ 25 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Inflammation is increased in DCM in vitro and vivo, and 6-G treatment reduces this inflammation. This confirms previous studies showing that inflammatory cytokines IL-1 β , IL-6, and TNF- α are elevated in DCM [ 34 , 35 ]. 6-G also has anti-inflammatory effects in other diseases such as sepsis, cerebral ischemia/reperfusion injury, and diabetic nephropathy [ 25 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been well established that DCM is attributed to various factors, including hyperglycemia, insulin disorder, inflammation, oxidative stress, cardiomyocyte apoptosis and others [9][10][11]. High glucose may directly mediate proinflammatory factors secretion and perpetuate the inflammatory process, causing cardiomyocyte hypertrophy, mitochondrial dysfunction, endoplasmic reticulum stress and death, fibroblast proliferation, collagen production and then promoting the development of DCM [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that ginsenoside Rb1 attenuated the levels of CRP, MCP-1, IL-1β, IL-6, and TNF-α in serum. This work demonstrated that ginsenoside Rb1 ameliorated MIRI of diabetic animals by regulating adipocytokine pathway and antioxidant pathway 35 . The left coronary artery of SD rats was occluded for 45 min followed by reperfusion for 2 h. Ginsenoside Rb1 showed a protective effect against MIRI.…”
Section: Ginsenoside Rb1mentioning
confidence: 67%